Evolution of Radiographic Parameters of Canine Passive Hip Laxity at 4, 6 and 12 months: A Study of 306 Dogs - Taroni, Mathieu; Genevois, Jean-Pierre; Viguier, Eric; Carozzo, Claude; Livet, Véronique; Baldinger, Arnaud; Cachon, Thibaut (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Objectives This article evaluates the variation in the distraction index (DI) and Norberg angle measurement with the femur in a neutral position and the hips distracted (distraction Norberg angle [DNA]) between 4, 6 and 12 months of age.Methods Radiographic data from dogs (n = 306) line-bred for favourable characteristics, including hip conformation, were reviewed. Dogs underwent stress radiographs, using a Vezzoni distractor, at 4, 6 and 12 months of age. The DI and DNA were calculated, and their evolution was studied for the total population and the sub-category of hips with a DI > 0.7.Results For the total population, the DI showed a significant increase from 4 to 6 months and a significant decrease at 12 months. For the hips with a DI > 0.7 at 4 months, DI at 6 and 12 months showed a significant decrease (0.14 and 0.26, respectively, on average). For the total population, the DNA followed the same pattern as the DI, and the values are significantly associated (p < 0.001).Clinical Significance The DI varies significantly from 4 to 12 months in dogs, and the time of radiographic evaluation of hip laxity may strongly influence the value of the DI. The DNA is strongly related to the DI, and its use as a more convenient indicator of hip laxity in dogs should be further investigated.
Keywords: canine hip dysplasia; distraction index; distraction Norberg angle